Pengaruh Budaya Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Koperasi BMT Binaul Ummah - Rafianti, Asti; Pranamulia, Agus; Fitrianti, Dewi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to determine the effect of Work Culture and Work Discipline on the Performance of BMT Binaul Ummah Cooperative Employees. The sample used in this study were all 25 BMT Binaul Ummah Cooperative employees located in Bogor City. The method used is multiple linear regression analysis to test the hypothesis. The results of the study indicate that employee work culture and employee work discipline have a significant effect on the performance of BMT Binaul Ummah Cooperative employees, both partially and simultaneously. Of the two independent variables, the work discipline variable has the most dominant effect on employee performance. Employee work culture explains 48% of the variation in employee performance, while work discipline explains 56% of the variation in employee performance. The F test shows that simultaneously, Work Culture and Work Discipline affect Employee Performance with an F value of 14.72 and a significance of p <0.01. The t test shows that the Work Discipline variable has the most dominant effect on employee performance with a t value of 3.98 and a significance of p <0.05. Thus, this study emphasizes the importance of a positive work culture and high work discipline in improving employee performance at the BMT Binaul Ummah Cooperative.